Metal / ceramic self-repairing agent, preparation method, self-repairing agent lubricating grease and application

By using metal/ceramic composite materials as self-repairing agents and evenly dispersing them in the grease through ultrasonic dispersion technology and polymer modification, the problem of performance stability reduction caused by nano-self-repairing agent agglomeration is solved, and the excellent anti-wear, friction reduction and self-repairing performance of the grease is achieved.

CN119703051APending Publication Date: 2025-03-28JINLING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411909832.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When existing greases wear on the frictional side surface, nano self-repairing agents are prone to agglomeration, resulting in a decrease in performance stability, significantly reducing the anti-wear and friction reduction effects, and the self-repairing function cannot perform normally.

Method used

The SiO2/SiC nanoceramic shell is synthesized by electroless plating, and ultrasonic dispersion technology and mechanical stirring are combined to ensure the uniform dispersion of the nanomaterial in the grease, and its dispersion is improved through polymer modification.

Benefits of technology

The uniform dispersion of nano self-repairing agents in the grease is achieved, which significantly improves the anti-wear, friction reduction and self-repairing performance of the grease, extends the service life of the equipment, and reduces maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119703051A_ABST
    Figure CN119703051A_ABST
Patent Text Reader

Abstract

The invention discloses a metal / ceramic self-repairing agent, a preparation method, self-repairing agent lubricating grease and application, and belongs to the field of mechanical lubrication.The preparation method of the metal / ceramic self-repairing agent comprises the steps that firstly, nano metal particles CuSn are synthesized; synthesizing a SiO2 / SiC nano ceramic shell layer on the surface of CuSn to obtain a metal / ceramic composite material with a core-shell structure; 2, the metal / ceramic composite material is placed in a mixed solvent of deionized water and absolute ethyl alcohol, polyvinylpyrrolidone is added, and a surface modified MC solution is obtained; adding sodium dodecyl benzene sulfonate and polyvinyl alcohol to obtain a prepolymer MC solution; and heating is conducted, acrylamide, methyl methacrylate, ammonium persulfate, N, N '-methylene bisacrylamide and tetramethylethylenediamine are added, and the polymer modified metal / ceramic P-MC nanometer self-repairing agent is obtained through a reaction. The lubricating grease containing the nanometer self-repairing agent forms a protective film on the surface of a friction pair, friction and abrasion are effectively reduced, the operation stability of equipment is improved, and the service life of the equipment is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of mechanical lubrication and relates to a grease, in particular to a metal / ceramic self-repairing agent and a preparation method, a self-repairing agent grease, and an application. Background Art

[0002] In today's highly developed modern industrial landscape, a wide variety of mechanical equipment is used across various fields. Friction and wear are inevitable in the friction pairs involved in their continuous operation. The friction generated by the relative motion of the contacting surfaces of these friction pairs during operation gradually wears away the component materials, altering their originally precise dimensions and shapes. This series of changes not only seriously disrupts the stable and normal operation of the mechanical equipment, causing adverse conditions such as stalling and increased vibration, but also significantly reduces the equipment's accuracy, resulting in inconsistent product quality and failing to meet the demands of high-precision industrial production. Furthermore, due to friction and wear, equipment components require more frequent replacement and maintenance, which significantly increases maintenance costs, including labor, material resources, and time.

[0003] To effectively address this issue, developing a grease containing nano-self-healing agents that simultaneously exhibits superior anti-wear and friction-reducing properties is crucial and crucial. This grease, with its nano-self-healing agent, rapidly accumulates at the site of wear and tear, initiating a complex series of physical and chemical reactions as soon as even the smallest signs of wear appear on the friction pair during equipment operation. This fills the wear pits and repairs the damaged surface, significantly reducing equipment wear. This allows the components of the equipment to maintain optimal working condition for a longer period of time, effectively extending the equipment's service life, reducing downtime caused by equipment failure or component replacement, and improving overall industrial production efficiency. Furthermore, the significantly reduced wear and tear on the equipment reduces the frequency of maintenance, significantly reducing the costs of maintenance personnel, parts, tools, and materials, resulting in significant economic benefits for the company's production operations.

[0004] However, the development and application of greases containing nano-self-healing agents present numerous technical difficulties and challenges. Due to the unique properties of nanomaterials, strong electrostatic and van der Waals forces exist between their particles. The interaction of these forces often causes nanomaterial particles to attract and aggregate within the grease system, forming large aggregates. Once nanomaterial particles aggregate, they alter the grease's otherwise uniform and stable physicochemical structure, significantly compromising its performance and stability. For example, aggregated nanoparticles may not be evenly dispersed within the grease, preventing them from reaching the friction pair surfaces at the critical moment when their anti-wear, friction-reducing, and self-healing properties are required. This significantly reduces the grease's anti-wear and friction-reducing effects, and impairs its self-healing properties. This not only impacts the grease's performance but also poses a potential risk to the normal operation of the equipment. Summary of the Invention

[0005] In response to the problems in the prior art, the present invention provides a metal / ceramic self-healing agent and its preparation method, self-healing agent grease, and its application. The grease has significant economic advantages in reducing the energy consumption of mechanical equipment, reducing maintenance expenses and improving production efficiency.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a metal / ceramic self-repairing agent for grease, comprising the following steps:

[0008] Step 1: synthesizing CuSn nanoparticles; synthesizing a SiO2 / SiC nanoceramic shell layer on the CuSn surface by chemical plating to obtain a metal / ceramic composite material with a core-shell structure;

[0009] Step 2: Place the metal / ceramic composite material in a mixed solvent of deionized water and anhydrous ethanol, add polyvinyl pyrrolidone, stir and ultrasonically obtain a surface-modified MC solution; add sodium dodecylbenzenesulfonate and polyvinyl alcohol to the surface-modified MC solution, and ultrasonically obtain a prepolymer MC solution; heat the prepolymer MC solution while stirring, and add acrylamide, methyl methacrylate, ammonium persulfate, N,N'-methylenebisacrylamide, and tetramethylethylenediamine to react to obtain a polymer-modified metal / ceramic P-MC nano self-healing agent, wherein the surface grafted polymer material is polymethyl methacrylate-acrylamide (PMMA-AM).

[0010] Furthermore, in step 1, the CuSn is synthesized by a DC arc plasma method, wherein a copper block and a tin block are placed in a powder making chamber of a DC arc plasma device, filled with hydrogen and argon at a volume ratio of 1:3 to 10, preferably 1:5, and a gas pressure of 0.01 to 0.04 MPa, preferably 0.03 MPa, and the copper block and the tin block are bombarded with a current intensity of 200 to 500 A, preferably 400 A, to generate plasma to synthesize the CuSn.

[0011] Furthermore, in step 1, the synthesis method of the metal / ceramic composite material is as follows: CuSn is dispersed as the "core" material in deionized water, SiC particles, polyvinyl pyrrolidone and sodium lauryl sulfate are added while stirring, ultrasonication is performed for 10 to 30 minutes, preferably 20 minutes, ethanol is added, the pH value is adjusted to acidic, ethyl orthosilicate is added dropwise, and after hydrolysis, it is heated to 50 to 70°C, preferably 60°C, and stirred to obtain a wet gel; drying at 80 to 120°C for 12 to 48 hours, preferably at 100°C for 24 hours, and grinding. , calcined at 350-550°C for 0.5-2h, preferably at 400°C for 1h, to obtain the metal / ceramic composite material; the amount ratio of CuSn, deionized water, SiC particles, polyvinyl pyrrolidone, sodium lauryl sulfate, ethanol and tetraethyl orthosilicate is 2-18g:50-200mL:0.5-2g:0.05-1g:0.05-1g:50-200mL:0.5-4g, preferably 12g:100mL:1g:0.3g:0.4g:100mL:2g.

[0012] Furthermore, in step 2, during the preparation of the surface-modified MC solution, the ratio of the metal / ceramic composite material, deionized water, anhydrous ethanol and polyvinyl pyrrolidone is 2-14 g: 50-200 mL: 50-200 mL: 0.05-1 g, preferably 10 g: 100 mL: 50 mL: 0.3 g;

[0013] During the preparation of the prepolymer MC solution, the ratio of the metal / ceramic composite material, sodium dodecylbenzenesulfonate and polyvinyl alcohol is 2-14 g: 0.05-1 g: 0.5-2 g, preferably 10 g: 0.5 g: 1 g;

[0014] During the preparation of the polymer-modified metal / ceramic P-MC nano self-healing agent, the heating temperature of the prepolymer MC solution is 60°C; the amount ratio of the metal / ceramic composite material, acrylamide, methyl methacrylate, ammonium persulfate, N,N'-methylenebisacrylamide and tetramethylethylenediamine is 2-14g:0.8-2g:0.5-3g:3-30mg:2-20mg:1-5μL, preferably 10g:1g:1g:12mg:10mg:2μL; the reaction is carried out under an inert atmosphere, and the reaction time is 0.5-2h, preferably 1h.

[0015] In a second aspect, the present invention provides a metal / ceramic self-healing agent prepared by the above-mentioned preparation method.

[0016] In a third aspect, the present invention provides a self-healing agent grease comprising the above-mentioned metal / ceramic self-healing agent.

[0017] In a fourth aspect, the present invention provides a method for preparing the above-mentioned self-healing agent grease: dodecyl hydroxystearic acid, oleic acid, lithium stearate, lithium hydroxide, deionized water and industrial gear oil are mixed, and then heated to perform a saponification reaction; the reaction product is heated to remove moisture therein; during the puffing process, industrial gear oil, dialkyl dithiophosphate molybdenum and the metal / ceramic self-healing agent are added, and the mixture is then cooled to obtain the self-healing agent grease.

[0018] Furthermore, during the saponification reaction, the amount ratio of dodecyl hydroxystearic acid, oleic acid, lithium stearate, lithium hydroxide, deionized water and industrial gear oil is 300-500g: 5-20g: 5-15g: 10-200g: 400-800mL: 900g, preferably 400g: 10g: 10g: 80g: 400mL: 900g; the industrial gear oil is 500N; the heating temperature is 110-140°C, preferably 125°C, and the time is 1-3h, preferably 2h; the heating temperature for dehydration is 140-170°C, preferably 155°C, and the time is 3-5h, preferably 4h.

[0019] Furthermore, in the expansion stage, the usage ratio of industrial gear oil, dialkyl dithiophosphate molybdenum and metal / ceramic self-repairing agent is 900g:5-20g:5-20g, preferably 900g:10g:8-10g; the industrial gear oil is 500N.

[0020] In a fifth aspect, the present invention provides the use of the above-mentioned self-repairing grease in friction reduction of friction equipment.

[0021] This self-healing grease is a grease designed specifically for industrial mechanical friction equipment. It not only possesses excellent anti-wear properties but also exhibits remarkable self-healing capabilities. Through formula design, combined with a specific self-healing agent and an oil-soluble organic compound, the present invention successfully enhances the protective and repairing effectiveness of the grease on the friction pair surface. Nano-copper has similar properties to the friction pair material and can instantly fill tiny scratches and pits on the surface during friction, allowing the self-healing agent to better blend with the friction pair surface. The SiC and SiO2 ceramic shells of the composite powder enhance the lubrication and self-healing capabilities of the grease. Polymethyl methacrylate-acrylamide has excellent self-lubricating properties and can significantly reduce the friction coefficient. It can also serve as a binder, helping the nano-self-healing agent stabilize in the grease and form a strong repair layer on the friction pair surface. Dialkyl molybdenum dithiophosphate is an oil-soluble organic compound containing active elements that can promote the adsorption and deposition of the self-healing agent on the friction pair surface. Through the chemical reaction of its active elements with the friction pair surface, a more stable friction-reducing film is formed, further reducing the friction coefficient and reducing the energy consumption and heat generation of the mechanical equipment. The grease developed by this invention is particularly suitable for industrial machinery and equipment with high requirements for friction, wear and self-repair performance, such as bearings, gears, and sliding guides. Its excellent performance will help improve the reliability and durability of mechanical equipment, reduce maintenance costs, and bring higher benefits to industrial production.

[0022] The present invention provides a metal / ceramic self-healing agent, a preparation method, a self-healing grease, and applications. Firstly, the present invention utilizes nano-metal / ceramic materials as self-healing agents, leveraging their small size and high surface energy to fill minute defects or cracks in the material, thereby repairing worn areas and improving the material's service life. Secondly, to achieve uniform dispersion of the nano-self-healing material in the grease, the present invention synthesizes nano-metal / ceramic materials and performs a polymer modification treatment to improve their dispersibility in the grease. Ultrasonic dispersion technology combined with mechanical stirring ensures uniform dispersion of the nano-material in the grease. Furthermore, by adjusting the grease formulation, the compatibility of the nano-material with the grease matrix is ​​enhanced. The nano-self-healing agent prepared by the present invention exhibits good compatibility with the grease, resulting in the grease exhibiting excellent friction reduction and self-healing properties. The grease containing the nano-self-healing agent forms a protective film on the surface of the friction pair, effectively reducing friction and wear and improving the operational stability and service life of the equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a SEM image of the MC composite material prepared in Example 1;

[0024] Figure 2 is a SEM image of the P-MC nano self-healing agent prepared in Example 1;

[0025] Figure 3 is a SEM image of the MC' composite material prepared in Comparative Example 1;

[0026] Figure 4 This is the SEM image of the P-MC' nano self-healing agent prepared in Comparative Example 1;

[0027] Figure 5 This is a surface morphology of the steel ball wear spot in the wear resistance test of the grease containing P-MC nano self-repairing agent in Example 2;

[0028] Figure 6 This is a surface SEM of the friction pair magnified 5000 times in the wear resistance test of the grease containing P-MC nano self-repairing agent in Example 2;

[0029] Figure 7 This is a surface morphology of the steel ball wear spot in the wear resistance test of the dialkyl dithiophosphate molybdenum base grease in comparative example 5;

[0030] Figure 8 This is a surface SEM of the friction pair magnified 5000 times in the wear resistance test of dialkyl dithiophosphate molybdenum base grease in comparative example 5. DETAILED DESCRIPTION

[0031] The present invention will be further described below with reference to specific embodiments.

[0032] Example 1

[0033] This embodiment provides a metal / ceramic self-repairing agent for grease, the preparation method of which comprises the following steps:

[0034] Step 1: Preparation of metal / ceramic composite materials:

[0035] Preparation of CuSn nanoparticles: Copper and tin blocks were placed in the powder making chamber of a DC arc plasma device and vacuumed to 3×10 -3 Pa, hydrogen and argon are then introduced into the powder preparation chamber at a volume ratio of 1:5, with a gas pressure of 0.03 MPa. An arc is connected in the powder preparation chamber, and at a current intensity of 400A, it bombards the copper and tin blocks to generate plasma. Copper vapor and tin vapor collide with argon molecules to form CuSn particles. The CuSn particles are then carried by the gas to the classification chamber for screening. Large-sized CuSn particles settle, while small-diameter CuSn particles are transported to the powder collection chamber with the gas. Under gas protection, the CuSn particles are collected by a scraper in a vacuum glove box. The powder yield is 40g / h, and the average particle size is 62nm.

[0036] Preparation of metal / ceramic composite materials: Weigh 12g of nano-metal particles CuSn and disperse them in 100mL of deionized water, place them in a magnetic stirrer, add 1g of SiC particles, 0.3g of polyvinyl pyrrolidone and 0.4g of sodium dodecyl sulfate while stirring, ultrasonicate for 20min, add 100mL of ethanol, add HCl to adjust the pH value to 4, add 2g of ethyl orthosilicate dropwise, hydrolyze and heat to 60°C and stir for 3h to obtain a wet gel. Then, place the wet gel in an oven at 100°C for 24h to dry the moisture to obtain a dry gel. Finally, grind the dry gel into fine powder, place it in a muffle furnace and heat at 400°C for 1h to obtain a metal / ceramic composite material, i.e., MC composite material, whose SEM is as follows: Figure 1 shown.

[0037] Step 2: Preparation of P-MC nano self-healing agent:

[0038] 10 g of MC composite material was placed in a mixed solvent of 100 mL of deionized water and 50 mL of anhydrous ethanol, 0.3 g of polyvinyl pyrrolidone was added, and the mixture was uniformly stirred by magnetic force and ultrasonically dispersed to obtain a surface-modified MC solution.

[0039] 0.5 g of sodium lauryl sulfate and 1 g of polyvinyl alcohol were added to the surface-modified MC solution, and the mixture was dispersed ultrasonically at 600 W for 30 min to obtain a prepolymer MC solution.

[0040] The prepolymer MC solution was stirred in a constant temperature magnetic stirrer and heated to 60 ° C. 1 g acrylamide, 1 g methyl methacrylate, 12 mg ammonium persulfate, 10 mg N, N'-methylenebisacrylamide, and 2 μL tetramethylethylenediamine were added. The mixed solution was reacted under nitrogen protection for 1 hour. After washing and centrifugation, it was placed in a vacuum box to dry to obtain a polymer-modified metal / ceramic P-MC nano self-healing agent. The surface grafted polymer material was polymethyl methacrylate-acrylamide (PMMA-AM). Its SEM is as follows: Figure 2 shown.

[0041] Comparative Example 1

[0042] This comparative example provides a metal / ceramic self-repairing agent for grease, and its preparation method comprises the following steps:

[0043] Step 1: Preparation of metal / ceramic composite materials:

[0044] The same method as in Example 1 was used to prepare CuSn nanoparticles.

[0045] Preparation of metal / ceramic composite materials: Weigh 12g of nano-metal particles CuSn and disperse them in 100mL of deionized water, place them in a magnetic stirrer, add 0.3g of polyvinyl pyrrolidone and 0.4g of sodium dodecyl sulfate while stirring, ultrasonicate for 20min, add 100mL of ethanol, add HCl to adjust the pH value to 4, add 2g of ethyl orthosilicate dropwise, hydrolyze and heat to 60°C and stir for 3h to obtain a wet gel. Then, place the wet gel in an oven at 100°C for 24h to dry the moisture to obtain a dry gel. Finally, grind the dry gel into fine powder, place it in a muffle furnace and heat at 400°C for 1h to obtain a metal / ceramic composite material, namely MC' composite material, whose SEM is as follows Figure 3 shown.

[0046] Step 2: Preparation of P-MC' nano self-repairing agent:

[0047] 10 g of MC' composite material was placed in a mixed solvent of 100 mL of deionized water and 50 mL of anhydrous ethanol, and 0.3 g of polyvinyl pyrrolidone was added and uniformly stirred by magnetic force and ultrasonically dispersed to obtain a surface-modified MC' solution.

[0048] 0.5 g of sodium lauryl sulfate and 1 g of polyvinyl alcohol were added to the surface-modified MC' solution, and the mixture was dispersed by ultrasound at 600 W for 30 min to obtain a prepolymer MC' solution.

[0049] The prepolymer MC' solution was stirred in a constant temperature magnetic stirrer and heated to 60 ° C. 1 g acrylamide, 1 g methyl methacrylate, 12 mg ammonium persulfate, 10 mg N, N'-methylenebisacrylamide, and 2 μL tetramethylethylenediamine were added. The mixed solution was reacted under nitrogen protection for 1 hour. After washing and centrifugation, it was placed in a vacuum box to dry to obtain a polymer-modified metal / ceramic P-MC' nano self-healing agent. The surface grafted polymer material was polymethyl methacrylate-acrylamide (PMMA-AM). Its SEM is as follows Figure 4 shown.

[0050] Example 2

[0051] The present embodiment provides a self-healing agent grease, the preparation method of which is as follows: 400g of dodecyl hydroxystearic acid, 10g of oleic acid, 10g of lithium stearate, 80g of lithium hydroxide, 400mL of deionized water and 900g of 500N industrial gear oil are mixed together in a refining kettle and heated at 125°C for 2h to carry out a saponification reaction. Then, the product after the reaction is heated at 155°C for 4h to remove the water therein. Then, during the expansion process, 900g of industrial gear oil with a viscosity grade of 500N, 10g of the metal / ceramic self-healing agent prepared in Example 1 and 10g of dialkyl dithiophosphate molybdenum are added, and the mixture is immediately cooled to prepare a grease containing a P-MC nano self-healing agent.

[0052] The wear resistance of the grease was evaluated by a four-ball friction and wear tester. First, the test was conducted at room temperature. The friction pair ran at a speed of 3000 r / min, the applied force was 500 N, the running time was 1 hour, the wear spot diameter was 0.51 mm, and the friction coefficient was 0.052. The surface morphology of the steel ball wear spot is as follows: Figure 5 As shown, the SEM image of the friction pair is magnified 5000 times. Figure 6 shown.

[0053] Example 3

[0054] The present embodiment provides a self-healing agent grease, the preparation method of which is as follows: 400g of dodecyl hydroxystearic acid, 10g of oleic acid, 10g of lithium stearate, 80g of lithium hydroxide, 400mL of deionized water and 900g of 500N industrial gear oil are mixed, placed together in a refining kettle, and saponified by heating at 125°C for 2h. Then, the product after the reaction is heated at 155°C for 4h to remove the water therein. Then, during the expansion process, 900g of industrial gear oil with a viscosity grade of 500N, 8g of the metal / ceramic self-healing agent prepared in Example 1 and 10g of dialkyl dithiophosphate molybdenum are added, and the mixture is immediately cooled to prepare a grease containing a P-MC nano self-healing agent.

[0055] The wear resistance of the grease was evaluated using a four-ball friction and wear tester. First, the test was conducted at room temperature, with the friction pair running at 3000 r / min, an applied force of 500 N, and a run time of one hour. The wear spot diameter was 0.33 mm, and the friction coefficient was 0.043.

[0056] Comparative Example 2

[0057] This comparative example provides a self-healing agent grease, the preparation method of which is as follows: 400g of dodecyl hydroxystearic acid, 10g of oleic acid, 10g of lithium stearate, 80g of lithium hydroxide, 400mL of deionized water and 900g of 500N industrial gear oil are mixed, put into a refining kettle together, and saponified by heating at 125°C for 2h. Then, the product after the reaction is heated at 155°C for 4h to remove the water therein. Then, during the expansion process, 900g of industrial gear oil with a viscosity grade of 500N, 8g of the metal / ceramic self-healing agent prepared in Comparative Example 1 and 10g of dialkyl dithiophosphate molybdenum are added, and the mixture is immediately cooled to prepare a grease containing P-MC' nano self-healing agent.

[0058] The wear resistance of the grease was evaluated using a four-ball friction and wear tester. First, the test was conducted at room temperature, with the friction pair running at 3000 rpm, an applied force of 500 N, and a run time of one hour. The wear spot diameter was 0.55 mm, and the friction coefficient was 0.136.

[0059] Comparative Example 3

[0060] This comparative example provides a self-healing agent grease, the preparation method of which is as follows: 400g of dodecyl hydroxystearic acid, 10g of oleic acid, 10g of lithium stearate, 80g of lithium hydroxide, 400mL of deionized water and 900g of 500N industrial gear oil are mixed, put into a refining kettle together, and saponified by heating at 125°C for 2h. Then, the product after the reaction is heated at 155°C for 4h to remove the water therein. Then, during the expansion process, 900g of industrial gear oil with a viscosity grade of 500N, 8g of MC composite material prepared in Example 1 and 10g of dialkyl dithiophosphate molybdenum are added, and the mixture is immediately cooled to prepare a grease containing MC nano self-healing agent.

[0061] The wear resistance of the grease was evaluated using a four-ball friction and wear tester. First, the test was conducted at room temperature, with the friction pair running at 3000 r / min, an applied force of 500 N, and a run time of one hour. The wear spot diameter was 0.95 mm, and the friction coefficient was 0.702.

[0062] Comparative Example 4

[0063] This comparative example provides a self-healing agent grease, and its preparation method is as follows: 400g of dodecyl hydroxystearic acid, 10g of oleic acid, 10g of lithium stearate, 80g of lithium hydroxide, 400mL of deionized water and 900g of 500N industrial gear oil are mixed, put into a refining kettle together, and saponification reaction is carried out by heating at 125°C for 2h. Then, the product after the reaction is heated at 155°C for 4h to remove the water therein. Then, during the puffing process, 900g of industrial gear oil with a viscosity grade of 500N, 8g of MC' composite material prepared in Comparative Example 1 and 10g of dialkyl dithiophosphate molybdenum are added, and the mixture is immediately cooled to prepare a grease containing MC' nano self-healing agent.

[0064] The wear resistance of the grease was evaluated using a four-ball friction and wear tester. First, the test was conducted at room temperature, with the friction pair running at 3000 rpm, an applied force of 500 N, and a run time of one hour. The wear spot diameter was 1.01 mm, and the friction coefficient was 0.781.

[0065] Comparative Example 5

[0066] This comparative example provides a molybdenum dialkyl dithiophosphate base grease. The preparation method comprises the following steps: 400 g of dodecyl hydroxystearic acid, 10 g of oleic acid, 10 g of lithium stearate, 80 g of lithium hydroxide, 400 mL of deionized water, and 900 g of 500N industrial gear oil are mixed in a refining kettle and heated at 125°C for 2 hours to perform a saponification reaction. The reaction product is then heated at 155°C for 4 hours to remove moisture. During the expansion process, 900 g of 500N viscosity grade industrial gear oil and 10 g of molybdenum dialkyl dithiophosphate are added, and the mixture is immediately cooled to prepare the base grease.

[0067] Finally, the wear resistance of the grease was evaluated by a four-ball friction and wear tester. First, the test was conducted at room temperature. The friction pair ran at a speed of 3000 r / min, the applied force was 500 N, the running time was 1 hour, the wear spot diameter was 1.51 mm, and the friction coefficient was 0.985. The surface morphology of the steel ball wear spot is as follows: Figure 7 As shown, the SEM image of the friction pair is magnified 5000 times. Figure 8 shown.

[0068] like Figure 7 and Figure 8 As shown in the figure, the base grease prepared in Comparative Example 5, which does not contain a self-repairing agent, has deeper wear marks on the surface of the steel ball under load. This indicates that the grease has poor anti-wear performance and lacks self-repairing ability, resulting in severe wear on the friction pair surface. Figure 5 and Figure 6 As shown, the grease containing P-MC nano self-repairing agent has shallower wear marks on the surface of the steel ball under load. The grease prepared in Example 2 has better wear resistance and self-repairing properties. The cavities on the wear surface of the friction pair of the steel ball are reduced and more sediments are produced. This shows that under the action of the external load, the self-repairing powder of the grease containing P-MC nano self-repairing agent continuously moves to the surface of the friction pair and produces sediments during the friction process, thereby effectively reducing the surface wear phenomenon. The metal ceramic composite powder with Cu as the core and SiC and SiO2 as the shell, the P-MC self-repairing agent after surface grafting of polymers and the active element of dialkyl dithiophosphate molybdenum have excellent tribological synergistic effects and have good stability in the grease. The P-MC self-repairing agent is well adsorbed on the surface of the friction pair and can form an excellent self-repairing layer, which further improves the self-repairing performance of the grease.

[0069] In the present invention, unless otherwise specified, the scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. In addition, the reagents, materials and operating procedures used herein are those widely used in the corresponding fields.

[0070] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art will be able to modify the technical solutions described in the aforementioned embodiments or substitute equivalents for some of the technical features. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.

Claims

1. A method for preparing a metal / ceramic self-repairing agent for grease, characterized in that: The following steps are involved: Step 1, synthesizing nano metal particles CuSn; Synthesize SiO2 / SiC nano-ceramic shell on the surface of CuSn to obtain a metal / ceramic composite material with a core-shell structure; Step 2: placing the metal / ceramic composite material in a mixed solvent of deionized water and anhydrous ethanol, adding polyvinyl pyrrolidone to obtain a surface-modified MC solution; adding sodium dodecylbenzene sulfonate and polyvinyl alcohol to the surface modified MC solution to obtain a prepolymer MC solution; The prepolymer MC solution is heated, and acrylamide, methyl methacrylate, ammonium persulfate, N,N'-methylenebisacrylamide and tetramethylethylenediamine are added to react to obtain a polymer-modified metal / ceramic P-MC nano self-healing agent.

2. The method for preparing the metal / ceramic self-repairing agent according to claim 1, characterized in that: In step 1, the CuSn is synthesized by a DC arc plasma method, wherein a copper block and a tin block are placed in a powder making chamber of a DC arc plasma device, and hydrogen and argon are filled in a volume ratio of 1:3 to 10, the gas pressure is 0.01 to 0.04 MPa, and the CuSn is synthesized at a current intensity of 200 to 500 A.

3. The method for preparing the metal / ceramic self-repairing agent according to claim 1, characterized in that: In step 1, the synthesis method of the metal / ceramic composite material is as follows: CuSn is dispersed in deionized water, SiC particles, polyvinyl pyrrolidone and sodium dodecyl sulfate are added while stirring, ultrasonication is performed, ethanol is added, the pH value is adjusted to acidic, ethyl orthosilicate is added dropwise, hydrolyzed and heated to 50-70° C., and stirred to obtain a wet gel; Drying and grinding, and calcining at 350-550° C. for 0.5-2 h to obtain the metal / ceramic composite material; The usage ratio of CuSn, SiC particles, polyvinyl pyrrolidone, sodium dodecyl sulfate and tetraethyl orthosilicate is 2-18g: 0.5-2g: 0.05-1g: 0.05-1g: 0.5-4g.

4. The method for preparing the metal / ceramic self-repairing agent according to claim 1, characterized in that: In step 2, the ratio of the metal / ceramic composite material to polyvinyl pyrrolidone is 2-14 g: 0.05-1 g; The usage ratio of the metal / ceramic composite material, sodium dodecylbenzene sulfonate and polyvinyl alcohol is 2-14 g: 0.05-1 g: 0.5-2 g; The heating temperature of the prepolymer MC solution is 60°C; the amount ratio of the metal / ceramic composite material, acrylamide, methyl methacrylate, ammonium persulfate, N,N'-methylenebisacrylamide and tetramethylethylenediamine is 2-14g: 0.8-2g: 0.5-3g: 3-30mg: 2-20mg: 1-5μL; the reaction is carried out under an inert atmosphere, and the reaction time is 0.5-2h.

5. The metal / ceramic self-healing agent obtained by the preparation method according to any one of claims 1 to 4.

6. A self-repairing grease, characterized in that: Contains the metal / ceramic self-healing agent as described in claim 5.

7. The method for preparing the self-repairing agent grease according to claim 6, characterized in that: Dodecyl hydroxystearic acid, oleic acid, lithium stearate, lithium hydroxide, deionized water and industrial gear oil are mixed and heated to perform saponification reaction; the product after the reaction is heated to remove water therein; During the expansion process, industrial gear oil, dialkyl dithiophosphate molybdenum and the metal / ceramic self-repairing agent are added, and then the mixture is cooled to obtain the self-repairing agent grease.

8. The method for preparing the self-repairing agent grease according to claim 7, characterized in that: During the saponification reaction, the dosage ratio of dodecyl hydroxystearic acid, oleic acid, lithium stearate, lithium hydroxide, deionized water and industrial gear oil is 300-500 g: 5-20 g: 5-15 g: 10-200 g: 400-800 mL: 900 g; Industrial gear oil is 500N; The heating temperature is 110-140°C and the time is 1-3 hours; The heating temperature for dehydration is 140-170°C and the time is 3-5 hours.

9. The method for preparing the self-repairing agent grease according to claim 7, characterized in that: In the expansion stage, the usage ratio of industrial gear oil, dialkyl dithiophosphate molybdenum and metal / ceramic self-repairing agent is 900g: 5-20g: 5-20g; Industrial gear oil is 500N.

10. Use of the self-repairing agent grease as claimed in claim 6 in friction reduction of friction equipment.